Why use storytelling in advertising? An experimental investigation of the effectiveness of storytelling in communicating corporate brand identity to consumers - BHAYANI, SAMIP (2015)
Stories have formed an integral part of our lives. The use of story has been made in various settings. We hear stories from everywhere. But the use of stories in marketing has been a trend in the recent times. Ranging from the individuals to brands, everyone is telling a story. Brand image and brand identity are the two concepts that the marketing managers are emphasising on. Trying to influence the consumers brand image through various marketing and advertising techniques, the marketers are trying to do this through using the brand identity as a weapon. However, a balance between the brand identity and the brand image is necessary. This research investigates the impact of storytelling on the gap between brand image and brand identity. It uses focus group experiment with a questionnaire to measure this variant. The use of stimulus material also has been done. The results from the experiment show that storytelling does impact the brand image and it helps bridge the gap between the two.